Taxonomy of sugarcane longhorn beetle Dorysthenes spp. derived from North and Northeast of Thailand - Thongphak, Duangrat; Hanlaoedrit, Chonlada (Asia-Pacific Journal of Science and Technology, 2017)
Taxonomy of Dorysthenes spp. was determined from 564 specimens of larva and adult. The specimens were collected from eight locations in Northeast and the North of Thailand, Kalasin, Khon Kaen, Chaiyaphum, Buriram Maha Sarakham, Udon Thani, Kamphaeng Phet and Nakhon Sawan. The specimens were identifi ed and described based on morphology both external and terminalia characters under stereomicroscope. The results show that the larvae of Dorysthenes spp. belong to subfamily Prioninae, however in this study the larvae can not be identifi ed into species level, since the larvae of all locations were not signifi cantly different in morphological characters. Two species of longhorn beetles were identifi ed based on morphological characters of adult. These included Dorysthenes granulosus and D. buqueti. In this study, D. granulosus is recorded fi rstly as pest of sugarcane in Thailand.